UF/IFAS Nutrient Management Series: Computational Tools for Field Implementation of the Florida Phosphorus Index - Okeechobee Watershed Area: CIR 1339/SS462, 6/2006 - Hurt, G. Wade; Mylavarapu, Rao S.; Boetger, S. P. (EDIS, 2006)
Circular 1339, a 48-page document by G. W. Hurt, R. S. Mylavarapu, and S. P. Boetger, provides many tables with numerical values for each of the various factors listed in the Florida P Index to be used in computations to aid planners in designing conservation plans related to land application of animal wastes. Contents: Introduction – Components of the P Index – Field Evaluation and Implementation for Okeechobee County – Resulting P Index – References – Appendix I: Runoff, Leaching Potentials, and K-Factors for County Soils. Published by the UF Department of Soil and Water Sciences, June 2006.